2019
DOI: 10.1002/gps.5163
|View full text |Cite
|
Sign up to set email alerts
|

Objective assessment of attention‐deficit/hyperactivity disorder in older adults compared with controls using the QbTest

Abstract: Objectives Attention‐deficit/hyperactivity disorder (ADHD) persists into old age, with prevalence rates of 2.8% to 3.3% in adults over 60 years of age. Most diagnostic assessment tools are not validated for older adults. The Quantified behavioral Test (QbTest) is an objective assessment for the core symptoms of ADHD and is validated for children and younger adults. We investigated whether the QbTest can be used to differentiate between older adults with ADHD and healthy controls. Methods Older adults aged 55 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Furthermore, the present data show that neuropsychological functions did not differ significantly between the groups in most of the measures, except for decreased vigilance performance (i.e., more omission errors) in the ADHD group. Pronounced vigilance impairments in the ADHD group underline the prominent role of vigilance and sustained attention tests in the clinical evaluation of ADHD, as it was demonstrated in a large body of empirical research on individuals with ADHD of various age groups (Bijlenga et al, 2019; Hall et al, 2016; Marchetta et al, 2008; Slobodin et al, 2020; L. Tucha et al, 2017) and advocated in an international consensus report (Fuermaier et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, the present data show that neuropsychological functions did not differ significantly between the groups in most of the measures, except for decreased vigilance performance (i.e., more omission errors) in the ADHD group. Pronounced vigilance impairments in the ADHD group underline the prominent role of vigilance and sustained attention tests in the clinical evaluation of ADHD, as it was demonstrated in a large body of empirical research on individuals with ADHD of various age groups (Bijlenga et al, 2019; Hall et al, 2016; Marchetta et al, 2008; Slobodin et al, 2020; L. Tucha et al, 2017) and advocated in an international consensus report (Fuermaier et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Ten studies with a control arm design were identified (Adamou et al, 2022;Bijlenga et al, 2019;Brunkhorst-Kanaan et al, 2020;Edebol et al, 2012Edebol et al, , 2013Emser et al, 2018;Groom et al, 2016;Hult et al, 2018;Pettersson et al, 2018;Söderström et al, 2014) (Table 2). All 10 studies assessed the ability of QbTest to discriminate between an ADHD population and one or more control populations.…”
Section: Review Of Studies Evaluating Discriminatory Abilitymentioning
confidence: 99%
“…QbTest was used as intended, but the study designs did not capture the value of adding QbTest in the diagnostic process or blinding the clinicians of the QbTest results in the control arm. Four studies reported data for a normative control population (two studies reported for a disconfirmed clinical population and two studies reported for confirmed differential diagnosis) (Bijlenga et al, 2019;Edebol et al, 2012Edebol et al, , 2013Emser et al, 2018). Six of the studies were conducted at a secondary or tertiary care facility (Adamou et al, 2022;Brunkhorst-Kanaan et al, 2020;Groom et al, 2016;Hult et al, 2018;Pettersson et al, 2018;Söderström et al, 2014).…”
Section: Review Of Studies Evaluating Discriminatory Abilitymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the criteria of the Diagnostic and Statistical Manual of Mental Disorders, ADHD can be divided into three categories: attention-deficit, hyperactive/impulse-control disorder, and combined ( 6 ). Studies have shown that the core symptoms of ADHD include inattention, hyperactivity and impulsiveness ( 7 ). At present, the main treatments for ADHD are drug therapy and non-drug therapy (mainly including behavioral therapy and cognitive behavioral therapy) and combination therapy, with the purpose of improving the core symptoms of children with ADHD and reducing behavioral problems.…”
Section: Introductionmentioning
confidence: 99%